1064 nm Nd:YAG long pulse laser after polidocanol microfoam injection dramatically improves the result of leg vein treatment: A randomized controlled trial on 517 legs with a three-year follow-up. (December 2014) - Moreno-Moraga, Javier; Smarandache, Adriana; Pascu, Mihail L; Royo, Josefina; Trelles, Mario A
Objective: To assess the efficacy and safety of a new method of clearing varicose veins in the long term. It consists of applying the long-pulsed Nd:YAG laser following the injection of polidocanol microfoam, in two consecutive sessions, treating both legs in full in each session. Method: Randomized, Polidocanol-controlled, blind evaluation clinical trial comparing the results between 79 legs treated with Polidocanol and 517 treated with Polidocanol + Laser. Photographs were taken preoperatively and at three months, two years and three years after treatment, as well as patient self-assessments. Results: Polidocanol + Laser is much more effective than polidocanol microfoam in clearing venulectasias with a diameter under 4 mm ( p < 0.001). After three years, clearing percentages of 89% (Class I veins), 94% (Class II veins) and 95% (Class III veins) are observed, in comparison to 15%, 18% and 17%, respectively when only polidocanol was applied. No unexpected adverse effects were found and 86% of patients stated they were Satisfied or Very Satisfied. Conclusion: The method leads to safe, fast and apparently permanent results. The treatment session lasts less than 1 h, and could become a first-choice treatment for the removal of all types of varicose veins with a diameter under 4 mm.